2001
DOI: 10.1603/0022-0493-94.6.1434
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Relative Importance and Effect of Lepidopterous Borers on Maize Yields in the Forest Zone and Mid-Altitude of Cameroon

Abstract: Geographic distribution, relative importance, and effect of lepidopterous stem and ear borers on maize, Zea mays L., were studied in the humid forest and the mid-altitude zones of Cameroon from 1994 to 1997. Six villages were chosen in the forest zone and grouped into three blocks representing gradients in human population density. A single block with three villages was chosen in the mid-altitude. Farmers' maize fields were surveyed during the vegetative growth phase for Busseola fusca (Fuller) egg batches, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
50
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 20 publications
(14 reference statements)
16
50
0
Order By: Relevance
“…Th us, whether total ear weight or grain alone should be used for yield loss assessments depends on the feeding habits of the borer species concerned. Th e multiple regression showed that stem diameter and nitrogen application were positively, and percent tunneling was negatively, related to grain yield, corroborating results by , , Gounou et al (1994) and Ndemah et al (2001). In general, tunnel length has shown to be a more precise and reliable measure of yield loss than insect numbers, because by the time the plants are sampled many borers might have already reached adulthood and left the plant or were killed by predators or parasitoids.…”
Section: Discussionsupporting
confidence: 85%
“…Th us, whether total ear weight or grain alone should be used for yield loss assessments depends on the feeding habits of the borer species concerned. Th e multiple regression showed that stem diameter and nitrogen application were positively, and percent tunneling was negatively, related to grain yield, corroborating results by , , Gounou et al (1994) and Ndemah et al (2001). In general, tunnel length has shown to be a more precise and reliable measure of yield loss than insect numbers, because by the time the plants are sampled many borers might have already reached adulthood and left the plant or were killed by predators or parasitoids.…”
Section: Discussionsupporting
confidence: 85%
“…However, B. fusca was reported to be common on P. purpureum in Central Africa (Cameroon) (Ndemah et al 2001a) and there may be agreement that host range of most insects is dynamic and often location and time-specifi c (Polaszek & Khan 1998). Unlike B. fusca, S. calamistis was recovered from many plant species confi rming its polyphagy corroborating reports from West and Central Africa (Ndemah et al 2001b). Th ough wild plants are attractive to ovipositing moths, larval survival and adult fecundity are generally low (Shanower et al 1993), which may explain the low populations observed in maize fi elds surrounded by wild hosts in Benin and Cameroon (Schulthess et al 1997;Schulthess et al 2001;Ndemah et al 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Most of these cereal crops serve as host plants for many stem borer insects among which Busseola fusca (Fuller 1901) (Lepidoptera: Noctuidae) is one of the most economically important pests (Polaszek & Khan 1998). B. fusca is an endemic species in subSaharan Africa with wide geographical distribution (Ajayi 1998;Moyal 1998;Ndemah et al 2001;Haile & Hofsvang 2001;Kfi r et al 2002). It is a major pest of sorghum (Sorghum bicolor [L.] Moench) and maize (Zea mays L.) (Poaceae).…”
mentioning
confidence: 99%